Aging under endocrine hormone regulation - Xing, Yutong; Xuan, Fan; Wang, Kaixi; Zhang, Huifeng (Frontiers in Endocrinology, 2023)
Aging is a biological process in which the environment interacts with the body to cause a progressive decline in effective physiological function. Aging in the human body can lead to a dysfunction of the vital organ systems, resulting in the onset of age-related diseases, such as neurodegenerative and cardiovascular diseases, which can seriously affect an individual's quality of life. The endocrine system acts on specific targets through hormones and related major functional factors in its pathways, which play biological roles in coordinating cellular interactions, metabolism, growth, and aging. Aging is the result of a combination of many pathological, physiological, and psychological processes, among which the endocrine system can achieve a bidirectional effect on the aging process by regulating the hormone levels in the body. In this paper, we explored the mechanisms of growth hormone, thyroid hormone, and estrogen in the aging process to provide a reference for the exploration of endocrine mechanisms related to aging.